2018
DOI: 10.1016/j.ekir.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Local Adipose-Associated Mediators and Adaptations Following Arteriovenous Fistula Creation

Abstract: IntroductionLocal inflammation is an important regulator of vascular remodeling. We hypothesized that adipose tissue adjacent to hemodialysis arteriovenous fistulae modulates maturation.MethodsDuring fistula creation, perivenous adipose was collected from 111 participants in the Hemodialysis Fistula Maturation Study. Nine adipose-associated mediators were measured. Duplex ultrasound was performed at 4 time points postoperatively from 1 day to first cannulation (10–26 weeks). Associations between logarithmicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…18 However, other studies hold the opposite conclusion. They found that IL6 in the adipose tissue around the fistula vein were associated with a reduction in the fractional vein diameter during the early time frame of 1 day to 2 weeks, 37 which shows that IL6 appears to have an early negative effect after AVF creation. In conclusion, the effect of IL6 on AVF maturation has been demonstrated, which is consistent with our experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, other studies hold the opposite conclusion. They found that IL6 in the adipose tissue around the fistula vein were associated with a reduction in the fractional vein diameter during the early time frame of 1 day to 2 weeks, 37 which shows that IL6 appears to have an early negative effect after AVF creation. In conclusion, the effect of IL6 on AVF maturation has been demonstrated, which is consistent with our experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…The sources and triggers of these circulating factors are not clear at the moment because many of them are ubiquitously produced by hematopoietic and nonhematopoietic cells (58,59,70,76,(84)(85)(86). Immune cell phenotyping studies are needed to assess activation of leukocyte populations and the balance of inflammatory and regulatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokine, such as monocyte chemotactic protein-1 (MCP-1), TNF-α, and interleukin 6 (IL-6), levels are also elevated in the AV fistula venous segment [ 22 , 48 ], which is positively associated with MMP-9 expression in vascular smooth muscle cells [ 49 , 50 , 51 ]. In addition, perivenous adipose MCP-1 and IL-6 levels are inversely related to early postoperative AV fistula veinous segment diameter changes [ 52 ]. MCP-1 knockout reduces AV fistula venous thickness and improves fistula patency, while TNF-α induces neointima after arterial injury via the TNF-α/MMP-9 axis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%